ENHANCING COASTAL RESILIENCY OF HYPOTHETICAL LAND RECLAMATION SCENARIOS WITH MANGROVE FOREST AND OYSTER REEF ASSESSED BY ADCIRC AND SWAN STORM SURGE MODEL - J. Rayo (Copernicus Publications, 2021)
This study aims to assess the effectiveness of mangrove forests and oyster reefs on reducing the damages from typhoons in hypothetical land reclamation scenarios in Atimonan, Philippines. Storm surge simulations were ran using ADCIRC and SWAN coupled model on the local government unit’s (LGU) land reclamation plan and the proposed crenulate bay reclamation plan, both with concrete seawall, mangrove forests and oyster reefs. Inputs to the model include modified topography and bathymetry, coastline, land cover, typhoon Durian data and tidal potential constituents. Simulations show that the crenulate bay reclamation plan is better by 39.15% than the LGU’s land reclamation plan on reducing typhoon winds and storm surge inundation extent induced by Typhoon Durian. However, this advantage comes with an additional implementation cost of 11.02%. This study is envisioned to help the land reclamation project of Atimonan LGU to be resilient against typhoon winds and coastal inundation.